Men with Crohn's disease may have an increased risk for head and neck squamous cell carcinoma - a nationwide register study - Harjunen Anni; Puolakkainen Enna; Laine Hanna K; Rautava Jaana (SPRINGER HEIDELBERG, 2022)
Objective Our goal was to study inflammatory bowel disease (IBD) patients' risk of head and neck squamous cell carcinoma (HNSCC), compared to general population.
Materials and methods We performed a retrospective nationwide register-based study of Finnish individuals diagnosed with IBD between the years 1995 and 2015. The standardized incidence ratio (SIR) of HNSCC was calculated by comparing the cohort's complementary age-year-sex-person-year incidence to that of the whole Finnish population.
Results About 70,567 patients were diagnosed with IBD (Crohn's disease or ulcerative colitis). Later, 89 of them were diagnosed with HNSCC with mean time of 6.82 years. The incidence of HNSCC was increased in IBD patients compared to the Finnish population expectation (SIR 1.3, 95% CI 1.065-1.614, P = 0.062). When calculating Crohn's disease and ulcerative colitis separately as well as men and women separately, the incidence was particularly increased for men with Crohn's disease (SIR 1.951, 95% CI 1.216-2.935, P = 0.025).
Conclusion An increased risk for HNSCC was found in men with Crohn's disease compared to the Finnish population expectations.
Clinical relevance This study provides information that would improve follow-up protocols and treatment guidelines of IBD.